Sexual dimorphism in wing shape of Dolichopus ungulatus (Linnaeus, 1758) and Hercostomus brevicornis (Staeger, 1842) with morphometric notes on wings of related species of Dolichopodinae (Diptera: Dolichopodidae) - Słomczyński, Kamil; Stępień, Anna; Wardziak, Natalia; Syratt, Maksymilian; Słowińska, Iwona (Zootaxa, 2026)
Wing venation provides important characters for systematic and phylogenetic studies of Dolichopodidae and may exhibit sexual dimorphism shaped by underlying biological mechanisms. This study examines sexual dimorphism in wing shape of two Dolichopodinae species, Dolichopus ungulatus and Hercostomus brevicornis, and compares male wing venation with that of closely related species, D. popularis and H. celer. Wing shape was analysed morphometrically using 138 wing images of four species collected in Poland, allowing quantitative assessment of intra- and interspecific variation. The results indicate pronounced sexual dimorphism in both studied species, with partial separation in H. brevicornis, and show significant differentiation in wing venation among related species. These findings highlight the utility of morphometric analysis in detecting subtle morphological differences between sexes and closely related taxa. These morphometric data may provide a useful basis for future studies on wing shape evolution and phylogenetic relationships within Dolichopodinae.